2018
DOI: 10.1080/13102818.2018.1512898
|View full text |Cite
|
Sign up to set email alerts
|

Members of R2R3-type MYB transcription factors from subgroups 20 and 22 are involved in abiotic stress response in tea plants

Abstract: Abiotic stresses, including extreme temperature, drought and salinity, seriously threaten the growth and development of tea plants. The tea plant fights against various threats to innate defensive systems by regulating the expression profiles of related anti-genes. R2R3-type MYB family transcription factors (TFs) contribute to plant defense against abiotic stresses. Five CsMYB TFs were identified from the tea plant according to the transcriptome database. Conserved motif analysis revealed that subgroups 20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…In this study, the expression of 11 AP2-EREBF and MYB genes were detected by qRT-PCR, and all of them appeared with higher transcript levels under alkaline stress (Figure 5). The results are in line with the studies that AP2-EREBF and MYB transcription factor families are involved in various abiotic stresses [30,31]. For example, a large number of AP2/ERF genes were induced in response to drought and salinity stresses in durum wheat [32].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the expression of 11 AP2-EREBF and MYB genes were detected by qRT-PCR, and all of them appeared with higher transcript levels under alkaline stress (Figure 5). The results are in line with the studies that AP2-EREBF and MYB transcription factor families are involved in various abiotic stresses [30,31]. For example, a large number of AP2/ERF genes were induced in response to drought and salinity stresses in durum wheat [32].…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that CRY1 has the function of regulating plant growth and development (Canamero et al 2006), and three genes were localised to chromosome 3 as MYB transcription factors, including LHY (MLOC_59912), CYP710A1 (MLOC_57804), and WRKY72 (MLOC_7939). The MYB transcription factors play a regulatory role in secondary metabolism, cell morphogenesis, the response to the environment, and the cell cycle (Wang et al 2003), and WRKY transcription factors -a class of transcription factors unique to plants -are involved in regulating growth and development, secondary metabolism, senescence, and the response to biotic and abiotic stresses (Shan et al 2018). The SP was localised on chromosomes 1, 5 and 7 and we analysed the segments with high phenotypic interpretation, locating a total of two genes, the SKIP11 (MLOC_72534) and TCP18 (MLOC_4614) transcription factors, to chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“…MYB transcription factors exhibit diverse functions in higher plants, including the regulation of various subbiological metabolic synthesis and abiotic stress responses [ 22 , 23 , 24 , 25 ]. MYB transcription factors have also been reported in tea plants [ 26 , 27 ]. CsMYB4a is potentially involved in the regulation of gene expression related to flavonoid biosynthesis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…CsMYB4a is potentially involved in the regulation of gene expression related to flavonoid biosynthesis [ 28 ]. CsMYB2 and CsMYB26 are two other regulatory genes involved in the biosynthesis of tea flavonoids [ 27 ].…”
Section: Introductionmentioning
confidence: 99%